Effectiveness of Aural-Oral Approach Based on Volubility of a Deaf Child with Late-Mapping Bilateral Cochlear Implants - Binos, Paris; Theodorou, Elena; Elriz, Thekla; Konstantopoulos, Kostas (My University, 2021)
Background: The purpose of this study was to investigate the effectiveness of aural-oral habilitation (AO) over the traditional speech-language therapy, based on the number of vocalization-volubility of a deaf child with late-mapping bilateral cochlear implants using sequential measurements. Methods: The spontaneous productions during child interactions were analyzed. The child (CY, 7;0 years old) with a mean unaided pure-tone average (PTA) hearing loss >80 dB HL was assessed by using an assessment battery. Study design consisted of two phases: (a) baseline (end of speech therapy) and (b) end of AO treatment. Protophones were analyzed via acoustical analysis using PRAAT software. Results: One-way repeated-measure ANOVAs were conducted within and between phases. The analyses revealed significant differences between the ‘phase’ and the vocalization outcome (F = 9.4, df = 1, p = 0.035). Post hoc analyses revealed the significant difference between the mean number of disyllable vocalizations of AO approach (p = 0.05). The mean number of vocalizations was calculated for each protophone type, but no other significant difference was measured. Conclusions: AO approach proved effective as measured through volubility. The outcome of this study is indicative and is a starting point for broader research.
Keywords: Cochlear implant; Speech therapy; Audiology; Deaf